Grades - Peter K. Rofes (Washington University Law Quarterly, 1995)
Make no mistake about it: Grades are a big deal in law school. A very big deal. Viewed from the perspective of students, just about every aspect of the law school experience-from job prospects to whether vending machines in the student lounge return the appropriate change-is affected by grades. In this respect, the law school represents a genuine meritocracy. Top grades earn students positions on the law review, invitations from respected law firms to come aboard for the summer, and membership in the school's chapter of the prestigious Almost-Justice Douglas H. Ginsburg Pizza, Bridge & Controlled Substances Society, a legal fraternity that meets twice a month in the library stacks. Mediocre grades cause students to forfeit desirable parking spaces in campus lots and receive comments such as "Mr. Schecter, how nice to see that the Academic Standing Committee has allowed you to return for your second year despite the fact that you have so little aptitude for the law" whenever professors pass them in the corridor.
Keywords: Law -- Study & teaching; Law -- Humor